2018
DOI: 10.1111/codi.13950
|View full text |Cite
|
Sign up to set email alerts
|

Complete mesocolic excision in right‐sided colon cancer does not increase severe short‐term postoperative adverse events

Abstract: The present study does not indicate that CME surgery is associated with an increased risk of severe adverse events such as 90-day mortality or reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Laparoscopic colorectal cancer surgery, which has an obvious minimally invasive advantage in the abdominal cavity, has become one of the most established surgical methods used for gastrointestinal cancer surgery [15,16] . For the better application of CMEs in laparoscopic hemicolectomies for right colon carcinoma cases, the following points have been summarized in the literature [8,12,17,18] and in our clinical experience. First, a CME presents the concept of fine anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic colorectal cancer surgery, which has an obvious minimally invasive advantage in the abdominal cavity, has become one of the most established surgical methods used for gastrointestinal cancer surgery [15,16] . For the better application of CMEs in laparoscopic hemicolectomies for right colon carcinoma cases, the following points have been summarized in the literature [8,12,17,18] and in our clinical experience. First, a CME presents the concept of fine anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…There was no association between plane of excision or tissue morphometry and post-operative complication, suggesting that more extensive tissue dissection potentially associated with 'good' quality surgery does not increase post-operative morbidity. Indeed, one concern over CME is the potential morbidity associated with the extensive tissue dissection that comes with central vascular ligation [20]; that said, as our surgeries were not routinely 'CVL dissections', this study cannot specifically add to this debate. The odds of postoperative complication were increased two-fold in patients undergoing open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of perioperative outcomes, the study coming from Peking University People's Hospital Beijing revealed no differences for postoperative complication rate, with less intraoperative blood loss and one day shorter hospital stay for the CME patients (see Table 2) (1). Analysis of the short-term postoperative adverse outcomes from the Swedish Colorectal Cancer Registry revealed a proportion of CME resections of 14.8% in the 90-day reoperation or mortality group vs. 19.5% in the control group (17). The odds ratio for short-term mortality or reoperation after CME was 0.82 (95% CI, 0.47-1.10, P=0.15), with lower values in the later part of the study and high-volume centers (17).…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…Analysis of the short-term postoperative adverse outcomes from the Swedish Colorectal Cancer Registry revealed a proportion of CME resections of 14.8% in the 90-day reoperation or mortality group vs. 19.5% in the control group (17). The odds ratio for short-term mortality or reoperation after CME was 0.82 (95% CI, 0.47-1.10, P=0.15), with lower values in the later part of the study and high-volume centers (17). Analysis of a consecutive patients series after the introduction of CME technique revealed a complication rate of 47%, with severe complications (grade III and IV Clavien Dindo) in 15% of cases (18).…”
Section: Perioperative Outcomesmentioning
confidence: 99%